2018
DOI: 10.3390/ma11071143
|View full text |Cite
|
Sign up to set email alerts
|

Improving Air-Stability and Performance of Bulk Heterojunction Polymer Solar Cells Using Solvent Engineered Hole Selective Interlayer

Abstract: In bulk heterojunction polymer solar cells (BHJ-PSCs), poly(3,4-ethylenedioxythiophene) doped with poly(styrene sulfonate) (PEDOT:PSS) is the most commonly used hole selective interlayer (HSIL). However, its acidity, hygroscopic nature, and the use of indium tin oxide (ITO) etching can degrade the overall photovoltaic performance and the air-stability of BHJ-PSCs. Solvent engineering is considered as a facile approach to overcome these issues. In this work, we engineered the HSIL using ethanol (ET) treated PED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 60 publications
(60 reference statements)
0
11
0
Order By: Relevance
“…Several metal-oxide based semiconductors, such as titanium dioxide (TiO 2 ) [ 15 , 16 , 17 , 18 ], zinc oxide (ZnO) [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], copper oxide (CuO) [ 28 , 29 , 30 , 31 ], zirconium oxide or zirconia (ZrO 2 ), cerium oxide (CeO 2 ) [ 29 ], tungsten oxide (WO 3 ), and tin oxide (SnO 2 ), have been successfully demonstrated as efficient photocatalysts for pollutant removal [ 32 , 33 , 34 ] and utilized in several other applications (energy, environment, and health) [ 35 , 36 , 37 ]. The semiconductor photocatalytic process includes irradiation of the semiconductor surface with a light having energy greater than the semiconductor’s bandgap.…”
Section: Introductionmentioning
confidence: 99%
“…Several metal-oxide based semiconductors, such as titanium dioxide (TiO 2 ) [ 15 , 16 , 17 , 18 ], zinc oxide (ZnO) [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], copper oxide (CuO) [ 28 , 29 , 30 , 31 ], zirconium oxide or zirconia (ZrO 2 ), cerium oxide (CeO 2 ) [ 29 ], tungsten oxide (WO 3 ), and tin oxide (SnO 2 ), have been successfully demonstrated as efficient photocatalysts for pollutant removal [ 32 , 33 , 34 ] and utilized in several other applications (energy, environment, and health) [ 35 , 36 , 37 ]. The semiconductor photocatalytic process includes irradiation of the semiconductor surface with a light having energy greater than the semiconductor’s bandgap.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2b showed the UV-vis absorbance of as-casted P3HT and PCBTDPP thin films, along with their respective PL spectrum of P3HT. The P3HT:PCBTDPP(0.2 wt.%):PC 61 BM film exhibited significantly improved absorption potential in the broadband range with high intensity, which is attributed to the complementary absorption spectra capability of PCBTDPP film (Figure 2b) [36,37]. PCBTDPP displayed strong light-absorbing ability from 615 nm to 700 nm, and the main absorption peaks of PCBTDPP was centered at 681 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The results revealed that the device with pristine PEDOT:PSS as HTL remains with 1% of the initial efficiency after 63 days of storage, whereas the device treated with TFA retains 25% of its initial efficiency. In another example, Xu et al [187] observed a decay of 72% of PCE after just 315 h for pristine device with PEDOT:PSS as HTL, whereas a 60% decay was observed for a device with solvent additives on PEDOT:PPS/ITO front contact after 315 h.…”
Section: π-Conjugated Polymers As Htls In Organic Solar Cellsmentioning
confidence: 99%